Koordinasi Camat dalam Pengembangan Ekonomi Kreatif di Kecamatan Regol Kota Bandung - Ero Suhara (FISIP Universitas Langlangbuana, 2019)
The problem in this study is about the sub-district coordination in the study of Creative Economy Development in Regol District in Bandung. This research speaks and focuses on coordination conducted by the camat in developing the creative economy, where the creative economy is one of the main focuses in the economy of Bandung, especially in the Regol district, where the Regol district has many potential sources of creative economy such as culinary, arts, architects, etc. Based on the first observation, the researchers found several indications of problems that occur in the coordination of creative economic development in Regol such as elements of the discussion of creative economy, the existence of miscommunication in coordination, and quite a number of creative economic actors who do not last long or out of business. Researchers try to examine by determining the formulation of problems such as, How the Coordination of Creative Economy Development is carried out, what factors are the concern, bat, and what efforts have been made from coordinating the development of the creative economy. To analyze the problem that the researcher has explained, the researcher chose the theoretical approach according to G.R Terry with the dimensions of synchronization, timing, harmonization, and the goals set in coordination. Based on the theory that the researchers have set, this study has the following proposition